2022
DOI: 10.1111/ejh.13811
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of venous thromboembolism and its associations in a large racially homogenous population of sickle cell disease patients

Abstract: To determine the prevalence of venous thromboembolism (VTE) among adult sickle cell disease (SCD) patients in Nigeria. Methods This was a multicentre retrospective study in which the medical records of adult SCD patients were reviewed. Information on demographics, steady‐state haemogram, clinical phenotypes, duration of follow‐up, history of VTE including risk factors and management was collected. Results Of the 509 SCD patients with a median (IQR) duration of follow‐up of 2 years, 10 (2.0%) had VTE (9 DVT and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
1
1
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
1
2
0
Order By: Relevance
“…Another Polish study (Dybowska et al) [34] also showed low awareness of VTE (40%) among their participants. Similar studies in Nigeria [35] and a global survey [36] were in a heterogeneous population. Equally, they showed low levels of DVT knowledge at 33.8% and 44% rates, respectively, although the number of pregnant women was not representative these studies.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Another Polish study (Dybowska et al) [34] also showed low awareness of VTE (40%) among their participants. Similar studies in Nigeria [35] and a global survey [36] were in a heterogeneous population. Equally, they showed low levels of DVT knowledge at 33.8% and 44% rates, respectively, although the number of pregnant women was not representative these studies.…”
Section: Discussionsupporting
confidence: 77%
“…In a previous similar study, Okoye et al [35], respondents also identi ed extended periods of immobility, increased serum cholesterol levels, and surgery as signi cant risk factors for VTE.…”
Section: Discussionmentioning
confidence: 77%
“…This underscores the need for further research to determine appropriate preventive measures for this demographic. Current guidelines recommend thromboprophylaxis only during antenatal hospital admissions [31], but a more comprehensive approach to risk stratification for prophylaxis outside of hospital admissions is warranted.…”
Section: Discussionmentioning
confidence: 99%